Antara Iman dan Kenikmatan: Konstruksi Gagasan Pascamodernisme Ariel Haryanto - Fariz Alnizar (Laboratorium Sosiologi Universitas Nahdlatul Ulama Indonesia Jakarta, 2020)
This article aims to describe the construction of Ariel Heryanto’s postmodernism ideas. Through in-depth observational studies on several articles, especially on the book entitled Identity and Pleasure: The Politics of Indonesian Screen Culture, this article concludes that post-modern epistemology is the foundation of Ariel’s analysis in seeing the development of popular culture in contemporary Indonesia. Ariel Heryanto used the postmodernism epistemology to see indications of popular culture. Indonesian identity which concerns to the meaning of being Indonesian Muslims, identity of minority (being Left and PKI), and expressions of choosing enjoyment while simultaneously affirming and building the identity in the context of middle-class Muslim fondness for K-Pop and K-Drama and other screen-based popular culture. Ariel Heryanto has succeeded in reading the phenomenon of a generation that try to redefine how to be a good Muslim, how to be a good citizen and at the same time remain a member of the global producer and consumer community.